Unveiling the DNA Barcoding of Threadfin Breams (Nemipteridae) at Oeba Fish Landing Site and Oesapa Fish Market in Kupang, East Nusa Tenggara - Wora, Umbu Domu; Wijayanti, Diah Permata; Widowati, Ita; Ginzel, Fanny Iriany; Nursalim, Nining; Kholilah, Nenik; Bachtiar, Muggi (Marine Science Department Diponegoro University, 2024)
Threadfin breams (Nemipteridae) are demersal fish species that constitute a significant catch for East Nusa Tenggara fishermen at the Oeba Fish Landing Site and Oesapa Fish Market, where they are landed year-round. Over the years, there has been a noticeable increase in the capture of threadfin breams, raising concerns about the potential impact on their genetic diversity. The ongoing trend could affect the region’s overall population structure of threadfin breams. This study addresses the need to identify threadfin breams in the landing above sites of threadfin breams through molecular analysis of mtDNA COI. The research involved the examination of 24 samples obtained from the Oeba Fish Landing Site and Oesapa Fish Market. The analysis revealed the presence of five distinct threadfin bream species: Nemipterus hexodon, N. japonicus, N. zysron, N. aurora, and Pristipomoides typus. The genetic distance between individual threadfin breams ranged from 0-0.8%, indicating a relatively close genetic relationship within the population. Also, phylogenetic tree reconstruction further delineated five distinct clades based on the species obtained from the samples. Given these findings, the study emphasizes the importance of sustainable threadfin bream capture to preserve genetic diversity. The results underscore the need for ongoing monitoring and management strategies to ensure the threadfin bream population’s long-term health and stability. Additionally, the study suggests that a more in-depth analysis of genetic diversity and the environmental factors influencing this species is warranted for a comprehensive understanding and effective conservation measures.